The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1039/d1qo01623g
|View full text |Cite
|
Sign up to set email alerts
|

Pyrylium salts acting as both energy transfer and electron transfer photocatalysts for EZ isomerization of activated alkenes and cyclization of cinnamic or biaryl carboxylic acids

Abstract: 2,4,6-Triarylpyrylium salts are stable, easily available and cheap. However, only their elec-tron transfer oxidation ability was explored. We herein report that they could perform both energy transfer and electron transfer...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…The series of dearomatization/rearomatization steps were supported by DFT calculations. Similar studies exercising both the concepts of photocatalysis in a single system have been reported, displaying dual roles of pyrylium salt, 168 Ir(ppy) 3 , 169 [Ru(bpy) 3 ]Cl 2 , 170 acridinium, 171 and riboflavin. 166…”
Section: Recent Applications Of Triplet–triplet Energy Transfer In Or...supporting
confidence: 71%
“…The series of dearomatization/rearomatization steps were supported by DFT calculations. Similar studies exercising both the concepts of photocatalysis in a single system have been reported, displaying dual roles of pyrylium salt, 168 Ir(ppy) 3 , 169 [Ru(bpy) 3 ]Cl 2 , 170 acridinium, 171 and riboflavin. 166…”
Section: Recent Applications Of Triplet–triplet Energy Transfer In Or...supporting
confidence: 71%
“…Overcoming typical monocyclic (4 + 2), (3 + 2), and (2 + 2) reaction manifolds, the presented strategy enables the one-step synthesis of challenging peri -bridged aza-acenaphthenes from simple quinolines and mono- and disubstituted alkynes. Adjoining seemingly remote carbon centers leverages a seldom explored energy-transfer/single-electron-transfer cascade using a single photocatalytic system. Photosensitization of the quinoline moiety permits the peri -addition process to be both thermodynamically feasible and kinetically competitive (compressed kinetic barrier) .…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Chen, Wang, Cheng and their coworkers disclosed a similar visible-light-induced cascade process for the E → Z isomerization and cyclization of cinnamic acids 81 utilizing pyrylium salt 83 as a dual-function PC for both EnT and SET processes (Scheme 21a). 77 Under the irradiation of blue LEDs, the group of Wang and Lu also reported a mild and effective cascade reaction of photocatalytic sequence isomerization, cyclization and C-H functionalization of 3-(2-hydroxyphenyl)acrylates 84 with ethers or thioethers 85 (Scheme 21b). 78 The protocol features good functional group tolerance and a broad substrate scope with respect to each reaction component, giving the desired 3-functionalized coumarins 86 in good yields in the presence of Ru(bpy) 3 Cl 2 •6H 2 O as the photocatalyst and TBHP as the oxidant.…”
Section: Visible Light-promoted Isomerization Of Alkenesmentioning
confidence: 99%